Measurement of IL-10 serum levels in BALB/c mice treated with beta-1,3 polyglucose or sulfadiazine and acutely infected by Toxoplasma gondii - Picka, M. C. M. [UNESP]; Calvi, S. A. [UNESP]; Lima, C. R. G. [UNESP]; Santos, I. A. T. [UNESP]; Marcondes-machado, J. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Acute infection by Toxoplasma gondii leads to suppression of cell-mediated immunity, facilitating chronic infection. One of the causes of immunosuppression is Interleukin-10 (IL-10) production. Glucan is used to stimulate phagocytosis. Our objective was to study IL-10 induction in male BALB/c mice with acute T. gondii BTU-2 strain infection, glucan immunostimulation, and sulfadiazine treatment. Animals were distributed into 7 groups: G1: infected with T. gondii; G2: infected with T. gondii and treated with sulfadiazine; G3: infected with T. gondii and immunostimulated with glucan; G4: infected with T. gondii, immunostimulated with glucan, and treated with sulfadiazine; G5: imunostimulated with glucan; G6: treated with saline; and G7: treated with sulfadiazine. IL-10 levels were determined by ELISA; the highest levels were found in G2, G3 and G4, and the lowest in G1 (p<0.001). Groups G1 to G5 and G7 had substantially higher levels than G6 (p<0.001). In this study, the highest IL-10 levels were found in groups treated with glucan.
Keywords: Toxoplasma gondii; interleukin-10; glucan; immune response; sulfadiazine